Analisis Dampak Cum Date Right Issue Terhadap Abnormal Return dan Volume Perdagangan Saham Di Bursa Efek Indonesia (Studi Kasus Pada Bursa Efek Indonesia Periode 2019-2021) - Yuliana, Khrisna Anggun (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: This study aims to determine whether there are differences in abnormal returns and volume. Background Problems: The impact of the Covid-19 pandemic where economic growth has resulted in almost all business sectors needing funds for a certain period of time with a sizable amount. Novelty: The implementation of the rights issue is able to cause investors to react to corporate action as indicated by the difference in abnormal returns and the difference in stock trading volume between before and after the cum date. Research Methods: Using event study analysis methods or techniques with data analysis using SPSS. Finding/Results: The results of this study indicate that there is a significant difference in abnormal stock returns before and after the cum date rights issue, but there is no significant difference in stock trading volume proxied by trading volume activity before and after the cum date rights issue. Conclusion: There is a significant difference in abnormal returns before and after the cum date rights issue on the IDX for the 2019-2021 period. It is hoped that investors will always pay attention and try to find information on every right issue corporate action so that the company gets the return as expected.